Putative purine nucleoside interacting residues in the malaria parasite purine uptake transporter PfENT1 are critical for transporter function. - Criselda Dillague; Myles H Akabas (PLoS ONE, 2023)
Malaria remains a major public health threat for billions of people worldwide. Infection with obligate intracellular, unicellular parasites from the genus Plasmodium causes malaria. Plasmodium falciparum causes the deadliest form of human malaria. Plasmodium parasites are purine auxotrophic. They rely on purine import from the host red blood cell cytoplasm via equilibrative nucleoside transporters to supply substrates to the purine salvage pathway. We previously developed a high throughput screening assay to identify inhibitors of the P. falciparum Equilibrative Nucleoside Transporter Type 1 (PfENT1). Screening a small molecule library identified PfENT1 inhibitors that blocked proliferation of P. falciparum parasites in in vitro culture. The goal of the current work was to validate a high-resolution model of PfENT1 predicted by the AlphaFold protein structure prediction program. We superimposed the predicted PfENT1 structure on the human homologue structure, hENT1, and developed a structure-based sequence alignment. We mutated the residues in PfENT1 aligned with and flanking the residues in hENT1 that interact with the purine analog, nitrobenzylthioinosine (NBMPR). Mutation of the PfENT1 residues Q135, D287, and R291 that are predicted to form hydrogen bonds to purine nucleosides eliminated purine and pyrimidine transport function in various yeast-based growth and radiolabeled substrate uptake assays. Mutation of two flanking residues, W53 and S290, also resulted in inactive protein. Mutation of L50 that forms hydrophobic interactions with the purine nucleobase reduced transport function. Based on our results the AlphaFold predicted structure for PfENT1 may be useful in guiding medicinal chemistry efforts to improve the potency of our PfENT1 inhibitors.